2016
DOI: 10.2501/ijmr-2016-026
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Shopper Transaction Data

Abstract: This paper applies the D Duplication Coefficient from the Duplication of Purchase Law as a benchmark to help investigate patterns in simultaneous product category purchases. Shopper transaction data enable a deep analysis of what goes into shoppers' baskets; however, robust benchmarks are critical to see patterns in such rich data. We demonstrate the application of D Duplication Coefficient data to 30,000-plus UK and US supermarket transactions. The cross-category benchmarks allow meaningful deviations to be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The second approach is based on the duplication factor (Goodhardt et al, 1984;Ehrenberg et al, 2004;Tanusondjaja et al, 2016), which normalizes the observed joint purchase probability [P(A \ B)] by the expected probability of purchase of both categories under independence, this is P(A)P(B). This metric is also referred to as lift in the association rules literature (Tan et al, 2002) and can be estimated as follows:…”
Section: Definitions and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The second approach is based on the duplication factor (Goodhardt et al, 1984;Ehrenberg et al, 2004;Tanusondjaja et al, 2016), which normalizes the observed joint purchase probability [P(A \ B)] by the expected probability of purchase of both categories under independence, this is P(A)P(B). This metric is also referred to as lift in the association rules literature (Tan et al, 2002) and can be estimated as follows:…”
Section: Definitions and Methodologymentioning
confidence: 99%
“…In particular, most of them show applications for no more than five product categories (Andrews and Currim, 2002;Erdem,1998;Heilman and Bowman, 2002;Ma et al, 2012;Manchanda et al, 1999;Russell and Kamakura, 1997;Russell and Petersen, 2000;Seetharaman et al,1999); while others require the estimation of a considerable number of choice models (Bell and Lattin, 1998;Chib et al, 2002). In contrast, Tanusondjaja et al (2016) apply the duplication of purchase law (Goodhardt et al, 1984 andEhrenberg et al, 2004) to study joint purchase patterns across 28 categories. For a given pair of categories, they compute a duplication factor that measures how the likelihood of buying one of the product categories increases if the other category is also purchased.…”
mentioning
confidence: 99%
“…According to Statistics Canada there exist 3 consumer profiles (see [WJ03], [WJ02], and [TNTK16]). The first profile represents consumers who buy only promotional items.…”
Section: Consumer Profilementioning
confidence: 99%
“…The Law of Double Jeopardy Ehrenberg, Goodhardt, & Barwise, 1990), household brand repertoire development (e.g. Stocchi, Banelis, & Wright, 2016;Trinh, 2014) and the extent to which brands and SKUs share their customers with competitors (e.g., Tanusondjaja, Nenycz-Thiel, & Kennedy, 2016).…”
Section: Introductionmentioning
confidence: 99%